2012
DOI: 10.2215/cjn.01170212
|View full text |Cite
|
Sign up to set email alerts
|

Circulating and Urinary microRNAs in Kidney Disease

Abstract: Summary microRNAs are small, noncoding RNAs that control gene/protein expression through target messengerRNA degradation and/or inhibition of protein synthesis. An array of experimental studies has shown the importance of microRNAs for disease initiation/progression. microRNAs are generally considered to act as intracellular modulators of gene expression. However, first studies in the cancer and cardiovascular field have elucidated that microRNAs are remarkably stable in the extracellular compartme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
68
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 90 publications
(71 citation statements)
references
References 41 publications
2
68
0
1
Order By: Relevance
“…MicroRNAs are 19–23‐nucleotide‐long noncoding single‐stranded RNA molecules that act as regulators of gene expression 11. Precursor microRNAs, known as pri‐microRNAs, are generated by RNA polymerase II and have as hallmark 5′ and 3′ poly‐A tails.…”
Section: Micrornas In Renal Physiology and Pathologymentioning
confidence: 99%
“…MicroRNAs are 19–23‐nucleotide‐long noncoding single‐stranded RNA molecules that act as regulators of gene expression 11. Precursor microRNAs, known as pri‐microRNAs, are generated by RNA polymerase II and have as hallmark 5′ and 3′ poly‐A tails.…”
Section: Micrornas In Renal Physiology and Pathologymentioning
confidence: 99%
“…In last few years, however, several studies have revealed the remarkable stability of extracellular miRNAs circulating in the blood or excreted in the urine and underscored their key importance as biomarkers of certain diseases (10,11 ). Intriguingly, circulating miRNAs may also modulate cellular transcriptional events by transferring genetic information from a donor cell to a recipient cell (12 ). The stability of circulating miRNAs depends on several critical mechanisms of miRNA transport, without which they are degraded by plasma RNAses within minutes (12 ).…”
mentioning
confidence: 99%
“…Intriguingly, circulating miRNAs may also modulate cellular transcriptional events by transferring genetic information from a donor cell to a recipient cell (12 ). The stability of circulating miRNAs depends on several critical mechanisms of miRNA transport, without which they are degraded by plasma RNAses within minutes (12 ). Circulating miRNAs are protected from degradation by inclusion into lipid or lipoprotein complexes, such as microvesicles/microparticles or exosomes (12 ).…”
mentioning
confidence: 99%
See 2 more Smart Citations